Knowledge and attitudes towards utilization of male condoms among youths in Entebbe regional referral hospital, Wakiso district. A cross-sectional study. - Tabu, Innocent; Masete, George; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Introduction Knowledge about condom use is generally widespread, as condoms are one of the most promoted methods for preventing both sexually transmitted infections. The study aims to assess the knowledge and attitude towards the utilization of male condoms among youths in Entebbe Regional Referral Hospital, Wakiso District. Methodology A descriptive cross-sectional study using quantitative methods was conducted among 40 youths selected through simple random sampling. Data were collected using structured and semi-structured questionnaires, checked for completeness, coded, and entered into Microsoft Excel (2022) for analysis, and findings were presented using frequencies, percentages, and graphical summaries. Results The majority, 18 (45%) of respondents were aged 25–29 years, and 8 (20%) were aged 18–24 years. 25 (62.5%) stated that awareness of PrEP or long-acting contraceptives reduces the need to use condoms, the majority 34 (85%) said condoms reduce the chance of STIs and unintended pregnancy, the majority 37 (92.5%) knew how to use condoms, while 3 (7.5%) did not. 26 (65%) strongly agreed that condoms reduce sexual pleasure. Regarding side effects, the majority, 21 (52.5%), disagreed that condoms have bad side effects. 22 (55%) strongly disagreed to use condoms. 33 (82.5%) strongly agreed that condoms prevent infections. Conclusion Although most youths (85%) demonstrated good knowledge of the protective benefits of condoms, a significant portion lacked adequate understanding of proper condom storage (55%), revealing a gap in practical knowledge essential for effective use. Recommendation Policy Makers should strengthen the implementation of comprehensive sexuality education at the community and school levels to address myths surrounding condoms and promote informed decision-making among youths.